Early development of synchrony in cortical activations in the human. (13th May 2016) - Koolen, N.; Dereymaeker, A.; Räsänen, O.; Jansen, K.; Vervisch, J.; Matic, V.; Naulaers, G.; De Vos, M.; Van Huffel, S.; Vanhatalo, S.
Highlights: We study the early development of cortical activations synchrony index (ASI). Cortical activations become increasingly synchronized during the last trimester. Interhemispheric synchrony increases more than intrahemispheric synchrony. Our EEG metric ASI can be directly translated to experimental animal studies. ASI holds promise as an early functional biomarker of brain networks. Abstract: Early intermittent cortical activity is thought to play a crucial role in the growth of neuronal network development, and large scale brain networks are known to provide the basis for higher brain functions. Yet, the early development of the large scale synchrony in cortical activations is unknown. Here, we tested the hypothesis that the early intermittent cortical activations seen in the human scalp EEG show a clear developmental course during the last trimester of pregnancy, the period of intensive growth of cortico-cortical connections. We recorded scalp EEG from altogether 22 premature infants at post-menstrual age between 30 and 44 weeks, and the early cortical synchrony was quantified using recently introduced activation synchrony index (ASI). The developmental correlations of ASI were computed for individual EEG signals as well as anatomically and mathematically defined spatial subgroups. We report two main findings. First, we observed a robust and statistically significant increase in ASI in all cortical areas. Second, there were significant spatial gradients in the synchrony in fronto-occipital and left-to-right directions. These findings provide evidence that early cortical activity is increasingly synchronized across the neocortex. The ASI-based metrics introduced in our work allow direct translational comparison to in vivo animal models, as well as hold promise for implementation as a functional developmental biomarker in future research on human neonates.